Digital Pop-Up Book Based on Problem Solving to Improve Learning Motivation of Fourth Grade Elementary School Students in Science and Social Studies (IPAS) - Eryang, Ni Wayan Putu Dila; Wibawa, I Made Citra; Dharmayanti, Putu Ari (Mimbar Ilmu, 2025)
The problems identified in the fourth grade of elementary school were the low learning motivation of students and the suboptimal use of learning media. These problems require solutions through the development of innovative and creative media that meet students’ needs. This study aims to develop a digital pop-up book based on problem-solving. The research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. Data collection methods included interviews, observations, and questionnaires. The research subjects were 31 fourth-grade elementary school students. The methods and techniques of data analysis used were qualitative descriptive analysis and quantitative descriptive analysis. The findings revealed that the problem-solving-based digital pop-up book obtained validity indices from media experts and material experts with qualifications categorized as highly valid. It also achieved a practicality index with qualifications categorized as highly practical. Furthermore, it significantly improved the learning motivation of fourth-grade students in Science and Social Studies (IPAS). These findings provide relevant solutions to the problems of low learning motivation and the limited use of learning media in supporting the learning activities of fourth-grade students. Thus, the problem-solving-based digital pop-up book is effective in enhancing students’ learning motivation and serves as an innovative medium to support the learning process in elementary schools.